2018
DOI: 10.1016/j.ijbiomac.2018.03.090
|View full text |Cite
|
Sign up to set email alerts
|

Probing the interaction interface of the GADD45β/MKK7 and MKK7/DTP3 complexes by chemical cross-linking mass spectrometry

Abstract: GADD45β is selectively and constitutively expressed in Multiple Myeloma cells, and this expression correlates with an unfavourable clinical outcome. GADD45β physically interacts with the JNK kinase, MKK7, inhibiting its activity to enable the survival of cancer cells. DTP3 is a small peptide inhibitor of the GADD45β/MKK7 complex and is able to restore MKK7/JNK activation, thereby promoting selective cell death of GADD45β-overexpressing cancer cells.Enzymatic MS foot-printing and diazirine-based chemical cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…To overcome this limitation, some new studies started to change strategy by focusing on inhibiting NF-κB target gene rather other NF-κB itself. For example, a D-tripeptide inhibitor, DTP3 (Ac-D-Tyr-D-Arg-D-Phe-NH 2 ), had been developed to targetedly inhibit the NF-κB target gene GADD45β, a NF-κB-regulated antiapoptotic factor [30,31]. This GADD45β inhibitor could disrupt the interaction of GADD45β with a JNK kinase MKK7, leading to restoring the MKK7 kinases activity and, ultimately, the JNK-mediated cell death pathway.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, some new studies started to change strategy by focusing on inhibiting NF-κB target gene rather other NF-κB itself. For example, a D-tripeptide inhibitor, DTP3 (Ac-D-Tyr-D-Arg-D-Phe-NH 2 ), had been developed to targetedly inhibit the NF-κB target gene GADD45β, a NF-κB-regulated antiapoptotic factor [30,31]. This GADD45β inhibitor could disrupt the interaction of GADD45β with a JNK kinase MKK7, leading to restoring the MKK7 kinases activity and, ultimately, the JNK-mediated cell death pathway.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the physical interaction of GADD45B/MKK7 blunts the activity of MKK7, leading to the suppression of JNK activity ( Papa et al, 2004 , 2008 ). Pharmacologically disrupting the GADD45B/MKK7 complex could restore MKK7/JNK activation in multiple myeloma ( Tornatore et al, 2014 ; Rega et al, 2018 ). Our data indicated that the p38 and JNK pathways, but not the ERK pathway, are activated by HG-mediated GADD45B overproduction in HK-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in the crystal structure of MKK7-ibrutinib complex, and further corroborated by our ITC measurement, ibrutinib bound to MKK7 in 2:1 stoichiometry, with the second molecule of ibrutinib bound within the newly discovered allosteric pocket at the N-terminal lobe of MKK7. Although the biological function of this allosteric pocket remains to be determined, previous studies have proposed that this Nterminal lobe region is involved in mediating protein-protein interactions in the context of MKK7 6 , as well as other binding partners, including GADD45β 47,48 . While the molecular details of the GADD45β binding site on the upper kinase still needs to be described, targeting the MKK7-GADD45β interaction, for example with the peptide-mimetic inhibitor DTP3, has been proposed as an alternative chemotherapeutic strategy for treatment of some cancer types with elevated GADD45β levels such as multiple myelomas 26 .…”
Section: Discussionmentioning
confidence: 99%